Synthesis and biological evaluation of novel N9-heterobivalent β-carbolines as angiogenesis inhibitors - Liang Guo; Qin Ma; Wei Chen; Wenxi Fan; Jie Zhang; Bin Dai (Taylor & Francis Group, 2019)
A series of novel N9-heterobivalent β-carbolines has been synthesized. All the novel compounds were tested for their anticancer activity against six tumour cell lines in vitro. Among these molecules, compounds 5b, and 5w exhibited strong cytotoxic activities with IC50 value of lower than 20 μM. Acute toxicities and antitumor efficacies of the selected compounds in mice were also evaluated, compounds 5b and 5w exhibited that tumour inhibition rate of over 40% in the Sarcoma 180 and Lewis lung cancer animal models. Preliminary structure-activity relationships (SARs) analysis indicated that: (1) C1-methylation and C7-methoxylation were favorable for increased activities; (2) 3-Pyridyl or 2-thienyl group substituent into position-1 of the β-carboline core, and the aryl substituent into another β-carboline ring might be detrimental to cytotoxic effects of this class compounds. Investigation of the preliminary mechanism of action demonstrated that compound 5b had obvious angiogenesis inhibitory effects in the chicken chorioallantoic membrane (CAM) assay.